Emphysematous rumenitis in a Japanese black calf caused by Clostridium perfringens with secondary Balantidium coli infection - HEGAZY, Asmaa A.; FUKE, Naoyuki; NAKAI, Mutsumi; KAKIYA, Miho; KONDO, Hiroaki; HIRAI, Takuya (Journal of Veterinary Medical Science, 2025)
A 4-month-old Japanese black calf exhibited anorexia and respiratory distress. Necropsy revealed a spongiform appearance of the rumen wall and histologically diagnosed as emphysematous rumenitis. The ruminal mucosa exhibited characteristic lesions of chemical rumenitis, so ruminal acidosis is suspected. Gram-positive bacilli were discernible on the degenerated ruminal mucosal surface and reacted with Clostridium species antibodies. Anaerobic cultures yielded Clostridium perfringens (C. perfringens), identified by multiplex polymerase chain reaction (PCR) as C. perfringens type A. The lumen and submucosa of the rumen showed a large ciliated trophozoite confirmed by PCR as Balantidium coli (B. coli). These findings suggest that ruminal acidosis leads to dysbiosis and allows C. perfringens type A to grow, causing emphysematous rumenitis and facilitating secondary B. coli infection.